The content of the course of modern programming languages in the context of higher education and the technology of its teaching (in the example of python) (Journal of Universal Science Research, 2023)
The article examines modern programming language courses in higher education, including their content, teaching technologies used, and Python's role as an example of a modern programming language. The article compares traditional programming language courses with modern programming language courses, showing the differences in content and teaching methods. The table shows a summary of the comparison between the two types of programming language courses.